DEFORMATION OF (MG0.9,FE0.1)SIO3 PEROVSKITE AGGREGATES UP TO 32 GPA - Merkel S.; Wenk H.R.; Badro J.; Montagnac G.; Gillet P.; Mao H.K.; Hemley R.J. (My University, 2003)
Room temperature investigations on the shear stress and deformation mechanisms of (Mg0.9Fe0.1)SiO3 perovskite are performed in situ up to 32 GPa using radial X-ray diffraction and the diamond anvil cell as a deformation apparatus. The uniaxial stress supported by the perovskite aggregate is found to increase continuously with pressure up to 10.9(+/-1.9) GPa at 32(+/-1) GPa. Our measurements show no development of significant lattice preferred orientations in the sample, which indicates that deformation by dislocation glide is not the dominant deformation mechanism under these conditions. Assuming that the underlying cause for seismic anisotropy in the deep Earth is elastic anisotropy combined with lattice preferred orientation, our results indicate that silicate perovskite deformed under the conditions of this experiment would not be the source of seismic anisotropy.
Keywords: HIGH PRESSURE; DEFORMATION; PEROVSKITE; SHEAR STRENGTH; TEXTURE; ANISOTROPY